β2-syntrophin is a Cdk5 substrate that restrains the motility of insulin secretory granules - Schubert, S; Knoch, K; Ouwendijk, J; Mohammed, S; Bodrov, Y; Jäger, M; Altkrüger, A; Wegbrod, C; Adams, M; Kim, Y; Froehner, S; Jensen, O; et al. (2010)
The molecular basis for the interaction of insulin granules with the cortical cytoskeleton of pancreatic β-cells remains unknown. We have proposed that binding of the granule protein ICA512 to the PDZ domain of β2-syntrophin anchors granules to actin filaments and that the phosphorylation/dephosphorylation of β2-syntrophin regulates this association. Here we tested this hypothesis by analyzing INS-1 cells expressing GFP-β2-syntrophin through the combined use of biochemical approaches, imaging studies by confocal and total internal reflection fluorescence microscopy as well as electron microscopy. Our results support the notion that β2-syntrophin restrains the mobility of cortical granules in insulinoma INS-1 cells, thereby reducing insulin secretion and increasing insulin stores in resting cells, while increasing insulin release upon stimulation. Using mass spectrometry, in vitro phosphorylation assays and β2-syntrophin phosphomutants we found that phosphorylation of β2-syntrophin on S75 near the PDZ domain decreases its binding to ICA512 and correlates with increased granule motility, while phosphorylation of S90 has opposite effects. We further show that Cdk5, which regulates insulin secretion, phosphorylates S75. These findings provide mechanistic insight into how stimulation displaces insulin granules from cortical actin, thus promoting their motility and exocytosis. © 2010 Schubert et al.